The EFTA Court: Ten Years On - Baudenbacher, Carl; Tresselt, Per; Orlygsson, Thorgeir (Bloomsbury Publishing (UK), 2005)
On the occasion of its tenth anniversary, the EFTA Court held a conference at which speakers were asked to reflect on the case law of the Court and its role in the European Economic Area (EEA). In the course of its work, the Court has acted as a driving force of integration under the EEA Agreement, by establishing general principles such as state liability and giving landmark judgments in several areas of European law. The essays in this volume, by leading experts and high-ranking representatives of national and European courts, cover areas such as the relationship between the principle of free movement and national or collective preferences on the EU/EEA and WTO levels, the relationship between the European courts and the Member States in European integration, homogeneity as a general principle of European integration, and the importance of judicial dialogue. In this regard, the sentence from President Skouris of the Court of Justice of the European Communities, who called the dialogue between the EFTA Court and the EC Court ‘a shining example of judicial cooperation’, could also serve as a motto for the present book.